AI-POWERED LEARNING: REVOLUTIONIZING COGNITIVE ABILITIES IN EDUCATION - Hariyanto S. Auna; Nuriyati Hamzah (Jurnal Ilmu Pendidikan dan Budaya, 2024)
AI-Powered Learning heralds a new era in the realm of education by revolutionizing the cognitive abilities of students. This article explores the positive impact of Artificial Intelligence (AI) technology on the learning process and the development of cognitive abilities in the context of education. Through this approach, AI can provide a personalized and adaptive learning experience, accommodating individual learning styles and stimulating cognitive growth. With an in-depth analysis of AI's implementation in education, this article discusses how this technology facilitates the development of cognitive skills, creativity, and problem-solving. The results indicate that AI-Powered Learning is not merely an educational tool but an agent of change capable of revolutionizing students' cognitive abilities, laying a robust foundation for an innovative and adaptive future of education.